Influence of fully miscible lubrication oil on flow boiling of CO? inside horizontal evaporator tubes - Wetzel, Markus (KIT Scientific Publishing, 2017)
Flow boiling heat transfer, pressure drop and flow pattern of CO?-POE oil mixtures were experimentally investigated in smooth and micro-fin tubes. The POE oil used features full miscibility in the range of operation investigated. The experimental data was evaluated based on mixture properties, used to evaluate and improve established predictive methods. The knowledge obtained contributes to understanding the influence of oil, which is essential for achieving an efficient evaporator design.